Potensi blue carbon pada tegakan pohon mangrove di pesisir Muna Barat - Rahman, Rahman; Sirajuddin, Nur Tasmiah; Lokollo, Frijona Febiola; Pasanea, Krisye; Fendjalang, Sophia Nonamanis Margaretha; Hulopi, Mahriyana (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
Mangrove ecosystems have an important role in mitigating climate change through carbon sequestration. This study aims to determine the blue carbon potential of mangroves on the coast of West Muna. The research was conducted by measuring mangroves density using the quadratic transect method (10 m x 10 m) and measuring stem diameter (DBH). The values ​​of carbon stock and carbon absorption were analyzed based on the biomass values ​​calculated using the allometric equation of each mangrove species. The results showed that the total biomass, stock, and carbon absorption of mangroves on the coastal areas of West Muna were 211.9 tones/ha, 99.21 tones C/ha and 363.77 tones CO2-eq/ha. The largest contributors to total biomass, stock, and carbon sequestration are R. stylosa and S. alba species. In contrast, the species with the lowest contributors are B. cylindrica and B. gymnorrhiza. Differences in the ability to store carbon in each species are influenced by the structure of the mangrove community, including density, stem diameter and root type. Mangroves of the Rhizophora species have good carbon absorption capabilities. Besides that, it can also adapt well to the environment, so it is very good to be managed and bred in climate change mitigation efforts.